Cancer Metastasis Molecular Mechanism and Clinical Therapy - Tutar, Yusuf; Tutar, Lütfi (IntechOpen, 2023)
Cancer mortality and morbidity are primarily brought on by metastasis. The ability of neoplastic cells to spread and colonize distant tissues is their most dangerous trait. Most malignancies are curable when they are detected early and have not spread outside of the original tissue. However, cancer is frequently incurable when tumor cells have created colonies elsewhere. Thus, the book content This book provides comprehensive information on cancer metastasis, along with references to specific cancer cases. The topics discussed include invasion by perturbation of cell-cell and cell-matrix adhesion, matrix degradation, motility, intravasation, extravasation, metastatic colonization, metastasis and angiogenesis. Molecular mechanisms, the metastatic process, and palliative bone metastasis therapy are also considered.